Cambodia - Report on the Observance of Standards and Codes (ROSC) : Accounting and Auditing - World Bank (World Bank, Washington, DC, 2022)
Cambodia has achieved remarkable economic development and political stabilization in recent years. Continuous high growth has heightened demand for high quality financial reporting and auditing in the corporate sector and in the government sector. This report on the observance of standards and codes accounting and auditing (ROSC A and A) report assesses the significant progress in the institutional framework for A and A since the previous ROSC A and A report in 2007. It analyses the accounting frameworks of listed companies, the banking and insurance sectors, state-owned enterprises (SOEs), and micro, small, and medium enterprise (MSMEs). The current report seeks to support the ongoing development of the financial reporting institutional framework in line with Cambodia’s national strategic development plan (NSDP) 2019-2023, which features good governance as a cross cutting theme. The report summarizes key findings, identifies gaps, and makes recommendations for consideration by the authorities to improve alignment with international standards and good practice. Unless otherwise specified, data and statistics quoted in this report relate to the 2019 calendar year. This reflects the data that was available and or applicable at the time the analysis was done.